Analisis Nilai Pendidikan Moral Cerpen “Istriku” Karya Etik, ST (Kajian Psikoanalisis Sigmund Freud) - Anjani, Nasywa Maudyna; Sihole, Irene Gabriella; Kurniawan, Eva Dwi (Kajian Bahasa dan Sastra (KABASTRA), 2024)
Based on Sigmund Freud's psychoanalytic theory, the "id, ego and superego" perspective, this research aims to explain the value of moral education in the ST story "My Wife by Ethics". Statements or quotations from texts that contain moral educational value are the data sources for this research. This study is qualitative in nature. The 4-page short story entitled My Ethics Work, ST, which was first published by the Student Press Institute PENDAPA Tamansiswa, is the data source for this research. Reading and note-taking methods were used to collect research data. Next, data analysis is carried out by reducing, presenting and drawing conclusions. The research results show that in the short story Istriku, the perspectives of the id, ego and superego are very important for moral education. In Totok's impulsiveness to borrow money and his threat to Ajik, the id perspective is reflected. Ego is shown when Totok cannot balance his needs with moral reality, such as in killing his wife. The superego is reflected in Totok's regret and Ajik's actions, which show awareness of social and moral norms. This research increases our understanding of the value of moral education in the short story Istriku, as well as its contribution to psychoanalysis and literary studies.